ANALISIS FAKTOR-FAKTOR PENYEBAB TIDAK BERFUNGSINYA PASAR WANIA DI DISTRIK WANIA - Rifky Andika Rado; Antje Tuasela (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to determine what factors influence the non-functioning of the Wania Market in Wania Distirik in Mimika Regency. The research method used is descriptive method. In this study, the data collection techniques used were observation and interview. While the data analysis instrument used is source triangulation. Evaluate the factors that influence the operation of Wania Market and its impact on Papuan mama-mama traders. The results show that the government has completed the licensing process required for market operations. However, cultural factors, such as the traders' habit of selling outside, are still an obstacle. Nonetheless, the facilities and infrastructure that have been prepared are quite complete although poorly maintained, there are still challenges in changing traders' preferences to switch to inside the market